Whey, steam rolled or whole oats, and fishmeal or meat and bone scraps for weaned pigs - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1981)
In two feeding trials, the use of whey, steam rolled or ground oats, fishmeal or meat and bone scraps in starter diets for the weaned pig was evaluated. In Trial I, pigs fed the basal corn-soybean meal diet gained 5% slower than pigs fed diets containing 8.75% whey, with either 8.75% steam rolled or ground oats and 2.5% fishmeal or meat and bone scraps. The pounds of feed required per pound of gain were similar for all diets, resulting in the cheapest gain with the corn-soybean meal basal diet. In Trial II, 192 lighter pigs were used (13 to 24 lbs., initial weight) with similar results. No significant difference was observed in rate of gain, average daily feed intake, or feed efficiency when whey, steamed rolled or ground oats, or fishmeal or meat and bone scraps were added to the basal ration. All diets contained approximately 17.5% crude protein, 1.08% lysine, .88% calcium, and .75% phosphorus. No beneficial effect seemingly is gained using more expensive feedstuffs (steam rolled oats and fishmeal) than more common feeds (ground oats and meat and bone scraps). The cheapest feed. cost per lb. of gain in both trials was observed with the basal corn-soybean meal fortified diet.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Whey; Steam rolled; Whole oats; Fishmeal; Meat and bone scraps; Weaning